Project-design Didactics: A documentary approach to narrative identity configurations in the teaching of Architecture (FAUD, UNMDP) (Praxis Educativa, 2018)
This article reports on the progress made in the context of a scholarship associated  o a local Research Project in the School of Architecture, Urbanism and Design at Mar del Plata State University. Such Project delves into the analysis of the semantic webs  university professors construct as they partake in practice communities devoted to the teaching of project design. The scholarship focuses on a particular kind of narrative: the formal curriculum presented by the three Chairs of a course in the Introductory Stage of the Architecture Undergraduate Program. Document analysis of such  materials has enabled access to the symbolic landscape as a means to understand teaching practices and the reasons that seem to underlie or support them.  Furthermore, light has been thrown on the specific didactics and the choreographies it assumes in this particular context.
Keywords: Project-Design Didactics; Semiotic Habitats; Narrative Territories; Practice Communities; Formal Curriculum